2022
DOI: 10.1097/cad.0000000000001396
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of lncRNA TCLlnc1 in gastric cancer predicts postoperative distant recurrence and poor survival

Abstract: TCLlnc1 was characterized as a lncRNA with oncogenic roles in T cell lymphoma, whereas its role in other diseases is unknown. We then explored the involvement of TCLlnc1 in gastric cancer. Paired gastric cancer and nontumor tissues from 66 gastric cancer patients were used to extract total RNA samples, which were used to perform RT-qPCRs to determine the expression of TCLlnc1. Plasma samples from these 66 gastric cancer patients and 66 healthy controls were also used to detect circulating TCLlnc1. Correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Furthermore, their overexpression was correlated with distant metastasis. These findings indicate that TCLlnc1 holds promise as a potential diagnostic and prognostic biomarker for GC (Hu et al, 2022).…”
Section: Lncrnas As Potential Biomarkers In Gcmentioning
confidence: 69%
“…Furthermore, their overexpression was correlated with distant metastasis. These findings indicate that TCLlnc1 holds promise as a potential diagnostic and prognostic biomarker for GC (Hu et al, 2022).…”
Section: Lncrnas As Potential Biomarkers In Gcmentioning
confidence: 69%
“…As a research hotspot and difficulty in the era of biological genomics, many studies have shown that tumor occurrence, metastasis, and tumor stage are closely related to the abnormal expression and mutation of lncRNAs [ 38 , 39 ]. Interestingly, recent studies have reported that lncRNAs also have some influence on tumor recurrence [ 40 , 41 ]. Therefore, due to their specific phrase in certain types of cancer, lncRNAs could represent a potential new class of prognostic, diagnostic, and therapeutic targets for treating cancer.…”
Section: Discussionmentioning
confidence: 99%